The effect of South African and international macro-economic variables on the South African Stock Market - Olivier, Alison Michell (College of Accounting, 2019)
This study aims to answer the empirical question of whether South African and US macroeconomic variables are predictors of returns on the South African stock market. The results add to a body of literature, assessing the period from 1996 to 2016, which includes comparative analysis of data pre-and post the 2008 financial crisis. Furthermore, both local and US macro-economic variables are assessed. Variables selected include 1) GDP (SA and US), 2) Interest Rates (SA and US), 3) Inflation (SA and US), 4) South African Money Supply, 5) Rand/Dollar Exchange Rate, and 6) FTSE Index. These variables are assessed on a monthly and quarterly basis, to provide further information on whether the relationships between the selected variables and the stock market are affected by the timing of the data or the level of noise within the data set. The variables are tested using time series Ordinary Least Squares (OLS) regression analysis. This analysis is used to assess predictive relationships. The results show that South African Interest rates and the RandDollar exchange rate have a statistically significant negative relationship with the South African stock market. Additionally, the South African interest rate appeared to hold a more statistically significant relationship with the stock market when the change in the rate was high. Furthermore, the FTSE Index shows a consistent statistically significant positive relationship. These findings provide valuable information to investors who, with further testing to determine exact time lags, can consider these predictive variables when making investment decisions, assuming weak form efficiency exists within the market.